The Impact Of Educational Strategies On Investment Literacy Among Higher Education Students - Alfito, Fiqih Mauzan; Dewi, Farida Ratna (UNIVERSITAS PAKUAN, 2025)
The number of capital market investors in Indonesia has significantly increased in recent years, indicating a growing public interest in investing. However, despite this growth, many investors are still exposed to losses from illegal investment practices, suggesting that investment literacy remains relatively low. This study aims to measure the level of investment literacy among undergraduate management students and to compare their literacy outcomes based on the application of Project-Based Learning (PJBL) and non-PJBL educational methods. The research adopts a mixed-method approach using quantitative data from questionnaires and qualitative insights from in-depth interviews. Data were analyzed using descriptive analysis and Mann-Whitney U test. The findings reveal that management students at IPB University possess a relatively high level of investment literacy. However, no significant difference was found between students taught using PJBL and those taught using non-PJBL methods. Integrating investment management courses into the curriculum contributes to enhancing student literacy. However, educational method differences do not significantly impact literacy levels. This study contributes to understanding the effectiveness of educational approaches in improving investment literacy among university students in a rapidly growing financial market.